2011
DOI: 10.1007/s10867-010-9209-1
|View full text |Cite
|
Sign up to set email alerts
|

New insights into bioprotective effectiveness of disaccharides: an FTIR study of human haemoglobin aqueous solutions exposed to static magnetic fields

Abstract: The aim of this study was the investigation of static magnetic field effects on haemoglobin secondary structure and the bioprotective effectiveness of two disaccharides, sucrose and trehalose. Samples of haemoglobin aqueous solutions, in the absence and in the presence of sucrose and trehalose, were exposed to a uniform magnetic field at 200 mT, which is the exposure limit established by the ICNIRP recommendation for occupational exposure. Spectral analysis by FTIR spectroscopy after 3 and 7 h of exposure reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…We previously reported that SH‐SY5Y differentiated cells, showing morphological and biochemical features of mature neurons are responsive to electromagnetic fields (EMFs) [Calabrò et al, ]. Given that the characteristic vibration spectra of cells can be due to the presence of abnormalities produced by external stress factors or disease states, we used FTIR spectroscopic techniques as an already proven powerful mean to study cell alterations, including the modification of protein secondary structures [Calabrò and Magazù, ; Magazù et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that SH‐SY5Y differentiated cells, showing morphological and biochemical features of mature neurons are responsive to electromagnetic fields (EMFs) [Calabrò et al, ]. Given that the characteristic vibration spectra of cells can be due to the presence of abnormalities produced by external stress factors or disease states, we used FTIR spectroscopic techniques as an already proven powerful mean to study cell alterations, including the modification of protein secondary structures [Calabrò and Magazù, ; Magazù et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was proved that also ELFEMFs and MWs can alter the secondary structure of proteins [10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…In addition, the experimental design adopted in previous experiments was used. [23][24][25] FTIR spectroscopic techniques were used to acquire information regarding the properties of gasoline compounds under exposure to a low-intensity SMF.…”
Section: Resultsmentioning
confidence: 99%